Traditional 3- to 5-Minute Interset Rest Periods May Not Be Necessary When Performing Fewer Repetitions Per Set: Using Clean Pulls as an Example - Jukic, Ivan; Tufano, James J (Journal of strength and conditioning research, 2022)
Jukic, I and Tufano, JJ. Traditional 3- to 5-minute interset rest periods may not be necessary when performing fewer repetitions per set: Using clean pulls as an example. J Strength Cond Res 36(11): 3015-3022, 2022-Three to 5 minutes of interset rest is often recommended for power-based exercises, but those recommendations are largely based on performing many repetitions per set, which can induce fatigue and require such lengthy rest periods. If the number of repetitions per set is reduced before fatigue ensues, interset rest periods may also be reduced without sacrificing performance. Therefore, the purpose of this study was to investigate the effects of this notion on barbell velocity and power output over multiple sets of clean pulls using different loads in strength-trained men. Fifteen strength-trained men performed 3 extended sets of 6 clean pulls using 80% (EXT80), 100% (EXT100), and 120% (EXT120) of power clean 1 repetition maximum with 180 seconds of interset rest and 9 short sets of 2 using 80% (SHT80), 100% (SHT100), and 120% (SHT120) with 45 seconds of interset rest. Peak velocity was greater during short set protocol than extended set protocol (80%: 1.74 ± 0.16 vs. 1.68 ± 0.15 m/s; 100%: 1.47 ± 0.15 vs. 1.41 ± 0.12 m/s; 120%: 1.21 ± 0.13 vs. 1.16 ± 0.15 m/s; p < 0.05). Furthermore, peak power was greater during SHT100 (1874.6 ± 267.5 vs. 1732.3 ± 250.4 W; p < 0.05) and SHT120 (1777.8 ± 226.1 vs. 1,650.4 ± 249.1 W; p < 0.05) than EXT100 and EXT120, respectively. Therefore, reducing the number of repetitions per set may allow for interset rest periods to also be reduced while better maintaining performance. However, the extent to which rest periods can be shortened warrants further investigation as total rest time was equal in this study.
Keywords: svalová síla; Rest; odpočinek; kosterní svaly; Muscle Strength; Male; únava; Muscle, Skeletal; vzpírání; lidé; Fatigue; mužské pohlaví; cvičení; odporový trénink; Weight Lifting; Humans; Exercise; Resistance Training